2006
DOI: 10.1002/job.418
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing returns on mentoring: factors affecting subsequent protégé performance

Abstract: SummaryThis study examined the effects of mentor success, relationship duration, and the amount of mentoring received on protégés' performance after the supervisory mentoring relationship had ended. Data collected from former protégés paired with objective measures of performance indicated that a mentor's success moderated the impact of mentoring functions received on subsequent protégé success. Additionally, the strength of these relationships depended on the length of the mentoring relationship. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 74 publications
(101 reference statements)
3
30
0
Order By: Relevance
“…Tepper (1995) has suggested that there may be differential relational agendas in supervisory mentoring relationships compared to nonmentoring relationships. In addition, Tonidandel, Avery, and Phillips (2007) have found that supervisory mentors' success in terms of their performance in the organization affects their protégés' performance. If the supervisory mentor is struggling in his or her position or perhaps experiencing his or her own job burnout due to the additional demands of mentoring, he or she may not be capable of contributing much to subordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Tepper (1995) has suggested that there may be differential relational agendas in supervisory mentoring relationships compared to nonmentoring relationships. In addition, Tonidandel, Avery, and Phillips (2007) have found that supervisory mentors' success in terms of their performance in the organization affects their protégés' performance. If the supervisory mentor is struggling in his or her position or perhaps experiencing his or her own job burnout due to the additional demands of mentoring, he or she may not be capable of contributing much to subordinates.…”
Section: Discussionmentioning
confidence: 99%
“…Success is largely assumed rather than demonstrated. Huybrecht et al [23], Gopee [24], Eby et al [27], Paglis et al [29], Tonidandel, Avery and Phillips [30], and more recently Williams et al [31] and Gray and Brown [32], indicate that there is little evidence to suggest that mentoring adds value to outcomes or indeed to improving quality and safety through clinical governance. However, Snowden and Hardy [26] and Snowden [28] allude to the potential benefits of mentorship on academic performance and learning for mentees and mentors in health and social welfare, suggesting that mentorship can enhance performance.…”
Section: Characteristics Of Mentoring In Supporting the Application Omentioning
confidence: 99%
“…Mentoring, or the provision of developmental support and guidance, to assistant coaches is an important component of being a head coach (Bloom et al 1998). Research indicates it can elevate salaries, increase promotions, and improve performance for protégés Tonidandel et al 2007;Underhill 2006). Diversified dyads (e.g., male mentor-female protégé), however, often function less effectively than those containing demographically similar pairs (Ragins 1997).…”
Section: Introductionmentioning
confidence: 97%